In the Pursuit of Green in COVID-19: Harnessing the Existing Talent to Pursue Green Corporate Entrepreneurship - Khan, Essa; Mubarik, Muhammad Shujaat; Shahid, Zubair Ali (Frontiers in Psychology, 2021)
The study was conducted to ascertain the role of talent management practices in promoting green corporate entrepreneurship in the context of COVID-19. The data was collected from 323 employees working in the manufacturing industry. The data analysis was done through Smart-PLS, both measurement and structural models were evaluated. The study found that talent management is related to green corporate entrepreneurship. The study also confirmed the mediating role of organizational engagement relating talent management with green corporate entrepreneurship. It is the first study that related talent management practices to green corporate entrepreneurship. Furthermore, it is the first study that examined the mediating role of organizational engagement relating talent management to green corporate entrepreneurship.